PENGARUH KOMPETENSI PENDAMPING DESA DAN PENGGUNAAN SISTEM KEUANGAN DESA TERHHADAP PENGELOLAAN KEUANGAN DESA - Djafarmaku, Muhamad Ravie Raflyzal; Kusuma, Indra Cahya; Susandra, Farizka (Komunitas Manajemen Kompetitif, 2025)
The aim of the research is to identify how the skills of village assistants and the use of the village financial system influence village financial management. A quantitative descriptive approach was used in the research process. Purposive sampling is the method used for sampling from 36 villages in Bogor Regency with a total sample of 109 village officials from each village. Data collection techniques through questionnaires. Multiple linear regression test and hypothesis test are the analysis methods used. Research findings show that in Bogor Regency, village financial management is simultaneously and partially influenced by the skills of village assistants and the use of the village financial system (SISKEUDES). Keywords: Competence of village assistants, village financial system